Micron silver powder and preparation method and application thereof

By leveraging the synergistic effect of specific reducing agents and dispersants, micron-sized silver powder with uniform particle size and high sphericity was prepared, resolving the contradiction between silver powder dispersibility and heat resistance, and improving the printing effect of conductive silver paste for internal electrodes and the quality of laminated products.

CN119260013AActive Publication Date: 2025-01-07ZHAOQING CHENYE ELECTRONICS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411382036.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

There is a contradiction between the dispersibility and heat resistance of existing silver powders, making it difficult to simultaneously possess both good dispersibility and heat resistance, which affects the printing effect of conductive silver paste for internal electrodes and the quality of products such as multilayer inductors and magnetic beads.

Method used

By using a reducing agent composed of glucose, hydroxylamine hydrochloride, and triethanolamine, and a dispersant composed of sodium polymethacrylate and N,N-dimethylstearamide, micron-sized silver powder with uniform particle size and high sphericity was prepared through specific synergistic effects of reduction and dispersion, and by controlling the reduction reaction conditions and pH value.

Benefits of technology

It achieves good dispersibility and heat resistance of micron-sized silver powder, improves the printing characteristics and firing compatibility of conductive silver paste for internal electrodes, reduces printing defects and internal cracks, and enhances the performance of products such as multilayer inductors and magnetic beads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005070134920000011
    Figure HDA0005070134920000011
  • Figure HDA0005070134920000012
    Figure HDA0005070134920000012
  • Figure HDA0005070134920000013
    Figure HDA0005070134920000013
Patent Text Reader

Abstract

The invention relates to the technical field of silver powder preparation, and particularly discloses micron-sized silver powder and a preparation method and application thereof. The preparation method comprises the following steps: dissolving 40-60 parts of silver nitrate in 180-220 parts of water, adding 40-60 parts of 25% (w / w) ammonia water to prepare a reaction solution, then dissolving 3-4 parts of glucose, 3-5 parts of hydroxylamine hydrochloride and 7-8 parts of triethanolamine in 180-220 parts of water, and adding 5-10 parts of sodium hydroxide to adjust the pH value to prepare a reduction solution; mixing the reducing solution and the reaction solution, and carrying out reduction reaction; and then sodium polymethacrylate and N, N-dimethyl stearamide are continuously added, and finally the micron-sized silver powder is obtained after filtering, cleaning and drying are conducted. The inner electrode conductive silver paste prepared from the micron-sized silver powder has good printing characteristics in the printing process, and meanwhile has good cofiring matching performance with a dielectric layer in the firing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silver powder preparation, and in particular to micron-grade silver powder and a preparation method and application thereof. Background Art

[0002] In the manufacture of laminated products such as laminated inductors and magnetic beads, the main key material is the conductive silver paste for the inner electrode. The conductive silver paste for the inner electrode is usually composed of conductive silver powder, resin, solvent and a variety of additives. The silver paste is printed on the dielectric diaphragm according to a preset pattern through a specific printing process such as screen printing, gravure offset printing or photolithography. Subsequently, after a series of complex processes such as lamination, water pressure, cutting, firing, end burning, electroplating, etc., the laminated inductor, magnetic beads and other products are finally formed. In this series of processes, the performance of the conductive silver paste for the inner electrode, especially its printing characteristics, co-firing characteristics with the dielectric layer and burning resistance, become the key factors affecting the quality of products such as laminated inductors and magnetic beads.

[0003] As the core component of the internal electrode conductive silver paste, the burning resistance and dispersibility of silver powder directly determine the overall performance of the internal electrode conductive silver paste. Among them, the burning resistance of silver powder directly affects the change curve of the firing shrinkage of the prepared internal electrode conductive silver paste, and then affects the firing matching between the internal electrode formed by the internal electrode conductive silver paste and the dielectric layer formed by the dielectric. If the matching is not appropriate, the inductor is very likely to have internal cracks or even cracks. In addition, the dispersibility of silver powder directly affects the printing effect of the internal electrode conductive silver paste. The printing performance of the internal electrode conductive silver paste prepared by the poorly dispersible silver powder is poor, and it is very easy to have poor electrode fullness, and even printing defects of lotus roots appear on the electrode. With the development of the miniaturization trend of electronic components, higher requirements are put forward for the dispersibility and burning resistance of silver powder. However, there is often a contradiction between the dispersibility and burning resistance of silver powder on the current market: silver powder with good dispersibility has relatively poor burning resistance due to its high activity; while silver powder with good burning resistance often has poor dispersibility, which affects the printing effect. This contradiction seriously restricts the further improvement of the performance of the internal electrode conductive silver paste, and also becomes a key technical problem in the manufacturing of multilayer products such as multilayer inductors and magnetic beads.

[0004] Therefore, it is necessary to develop a silver powder that has both good dispersibility and good burning resistance, to further improve the performance of the internal electrode conductive silver paste, to further improve the performance of products such as multilayer inductors and magnetic beads, and to promote the miniaturization of electronic components. Summary of the invention

[0005] In order to develop a silver powder with both good dispersibility and excellent burning resistance, the present application provides a micron-level silver powder and its preparation method and application. The present application selects a specific reducing agent and dispersant, and through the coordinated cooperation of the reducing agent and the dispersant, the uniform dispersion and stable growth of the silver powder in the preparation process are achieved, thereby preparing a micron-level silver powder with high sphericity and uniform particle size distribution, thereby preparing a micron-level silver powder with both good dispersibility and good burning resistance. The conductive silver paste for the internal electrode prepared by the micron-level silver powder of the present application has good printing characteristics during the printing process, and has good co-firing matching with the dielectric layer during the firing process, effectively avoiding the problem of internal cracks or cracking between the internal electrode and the dielectric layer, and is not prone to poor electrode fullness or lotus-shaped printing defects, further improving the overall performance of products such as laminated inductors and magnetic beads.

[0006] In the first aspect, the present application provides a method for preparing micron-sized silver powder using the following technical solution: A method for preparing micron-sized silver powder comprises the following steps: Step 1: Based on the mass fraction of the reaction solution, 40-60 parts of silver nitrate are dissolved in 180-220 parts of water, and 40-60 parts of 25% (w / w) ammonia water are added to prepare a reaction solution; Step 2: Based on the mass fraction of the reducing solution, 3-4 parts of glucose, 3-5 parts of hydroxylamine hydrochloride and 7-8 parts of triethanolamine are dissolved in 180-220 parts of water, and 5-10 parts of sodium hydroxide are added to adjust the pH value to prepare a reducing solution; Step 3: Under stirring, completely add the reducing solution into the reaction solution to carry out a reduction reaction; Step 4: After the reducing solution is added, sodium polymethacrylate and N,N-dimethyl stearamide are added, and the mixture is stirred evenly to obtain a dispersion, wherein the mass ratio of the silver nitrate, sodium polymethacrylate and N,N-dimethyl stearamide is 100:(0.31-0.64):(0.19-0.5); Step 5: Filter, wash and dry the dispersion to obtain micron-sized silver powder.

[0007] In the above technical scheme, the present application adopts a reducing agent compounded with glucose, hydroxylamine hydrochloride and triethanolamine, and a dispersant compounded with sodium polymethacrylate and N,N-dimethyl stearamide, and realizes uniform dispersion and stable growth of micron-sized silver powder through the synergistic effect of specific reducing agents and dispersants. Such micron-sized silver powder not only has good dispersibility, but also has good burning resistance. In the reduction reaction, the compound use of glucose, hydroxylamine hydrochloride and triethanolamine not only improves the reduction efficiency, but also helps to control the particle size and shape of the silver powder; the addition of sodium polymethacrylate and N,N-dimethyl stearamide, the synergistic reducing agent further improves the dispersibility and stability of the silver powder, and helps to prevent the silver powder from agglomerating during the subsequent drying and sintering process, thereby maintaining the dispersibility and uniformity of the silver powder. Through this synergistic effect, the micron-sized silver powder finally obtained in the present application has a higher sphericity and uniform particle size distribution. Such micron-sized silver powder has lower surface activity and higher dispersibility, and has both good dispersibility and good burning resistance. It can show excellent printing characteristics and firing matching in the internal electrode conductive silver paste. The prepared internal electrode conductive silver paste is not only suitable for screen printing in multilayer inductors, but also helps to improve the electrode fullness during the printing process and reduce printing defects. It can also perform well in matching with the dielectric firing of inductor products under long-term firing conditions at 900°C. This further improves the performance of multilayer inductors, magnetic beads and other products, and promotes the miniaturization of electronic components.

[0008] Preferably, in step 2, sodium hydroxide is added to adjust the pH value to within the range of 13-14, and after adding sodium hydroxide, stirring is performed at 50-150 rpm for 15-30 minutes to obtain a reducing solution.

[0009] In the above technical solution, the present application can ensure that the activity of the reducing agent is optimized by adjusting the pH value to a specific range, so that the particle size distribution of the silver powder is more uniform, thereby improving the uniformity and reaction efficiency of the silver powder, and further optimizing the dispersibility and sphericity of the silver powder. At the same time, under the adjustment of the pH value, the occurrence of side reactions is reduced, ensuring the purity and quality of the silver powder.

[0010] Preferably, in step 3, the mass ratio of the reducing liquid to the reaction liquid is 1:(1-1.5).

[0011] In the above technical solution, the present application can ensure the full progress of the reduction reaction by controlling the mass ratio of the reducing liquid to the reaction liquid within the range of 1: (1 to 1.5), avoiding the unreacted silver nitrate residue in the reaction liquid, thereby improving the yield and purity of the silver powder. At the same time, it helps to form uniform silver powder particles and reduce agglomeration, so that the final micron-sized silver powder has better dispersibility and burning resistance.

[0012] Preferably, step 3 is as follows: respectively adjusting the temperature of the reducing solution and the reaction solution to 30-40° C., and then completely adding the reducing solution to the reaction solution within 1-10 min under stirring at 50-150 rpm to carry out a reduction reaction.

[0013] In the above technical scheme, the present application controls the temperature of the reducing liquid and the reaction liquid within the range of 30-40°C and adds the reducing liquid to the reaction liquid within 1-10 minutes at a stirring speed of 50-150rpm, thereby ensuring the smooth progress of the reduction reaction, helping to form silver powder particles with uniform particle size distribution and higher sphericity, and further improving the dispersibility and burning resistance of the micron-sized silver powder.

[0014] Preferably, in step 4, continuing to stir evenly means stirring at 50-150 rpm for 30-40 min at a temperature of 30-40°C.

[0015] In the above technical scheme, by controlling the dispersion liquid to be stirred at a temperature of 30-40°C and a stirring speed of 50-150 rpm for 30-40 minutes, it is possible to ensure that sodium polymethacrylate and N,N-dimethylstearamide are fully mixed with the silver powder particles, and ensure that the sodium polymethacrylate and N,N-dimethylstearamide fully modify the surface of the silver powder, thereby further improving the dispersibility and stability of the silver powder, further preventing the silver powder from agglomerating during the subsequent drying and sintering process, and maintaining the dispersibility and uniformity of the silver powder.

[0016] Preferably, the step 5 is as follows: filtering, washing, and drying the dispersion, washing it twice with banana water, and drying it to obtain micron-sized silver powder.

[0017] In the above technical scheme, the present application uses banana water for secondary cleaning after filtering, washing and drying the micron-sized silver powder, so as to better remove the organic matter and impurities remaining on the surface of the micron-sized silver powder, further improve the conductivity of the micron-sized silver powder, and further improve the dispersibility and printing characteristics of the micron-sized silver powder in the conductive silver paste of the internal electrode.

[0018] Preferably, the median particle size of the micron-sized silver powder is below 3.0 μm.

[0019] In the above technical scheme, the present application controls the median particle size of the micron-sized silver powder to be below 3.0 μm, so that the micron-sized silver powder can better combine with the dielectric material, reduce shrinkage and cracks after firing, and ensure that the micron-sized silver powder is suitable for printing the internal electrode conductive silver paste of narrow-width lines, especially for printing very fine lines with a line diameter of about 15 μm.

[0020] In the second aspect, the micron-sized silver powder provided in the present application adopts the following technical solution: A micron-sized silver powder is prepared by using the method for preparing the micron-sized silver powder described in the first aspect.

[0021] In the above technical scheme, the micron-sized silver powder prepared in the present application has uniform particle size distribution, high sphericity, good dispersibility and burning resistance, good fluidity during screen printing, can significantly reduce printing defects, and is suitable for the manufacture of various electronic components.

[0022] In the third aspect, the application of a micron-sized silver powder provided in the present application adopts the following technical solution: The invention discloses an application of micron-sized silver powder for preparing conductive silver paste for internal electrodes.

[0023] In the above technical solution, the application of the micron-sized silver powder prepared in this application in the conductive silver paste for the internal electrode not only improves the electrode fullness during the printing process, but also has excellent matching performance with the dielectric of the inductor product under high-temperature firing conditions, significantly improving the performance of electronic components such as laminated inductors and magnetic beads. In addition, due to the high dispersibility and good burning resistance of the micron-sized silver powder, the conductive silver paste for the internal electrode has better printing characteristics during the printing process, thereby further promoting the miniaturization and high performance of electronic components.

[0024] Preferably, the conductive silver paste for the inner electrode comprises the following components: 4wt%-6wt% ethyl cellulose, 8wt%-12wt% terpineol, and 80wt%-90wt% micron-sized silver powder.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application provides a method for preparing micron-sized silver powder. The present application optimizes the formula of a reducing agent and a dispersant, and specifically selects a reducing agent formed by a compound of glucose, hydroxylamine hydrochloride and triethanolamine, and a dispersant formed by a compound of sodium polymethacrylate and N,N-dimethylstearamide. Through the synergistic effect of such reducing agent and dispersant, the uniformity of particle size distribution and high sphericity of the micron-sized silver powder are ensured, and good dispersibility and firing resistance of the micron-sized silver powder are achieved. Such micron-sized silver powder is suitable for high-temperature firing at 900°C.

[0026] 2. This application reduces the occurrence of side reactions by adjusting the pH value to a specific range, ensures the purity and quality of the silver powder, and further optimizes the dispersibility and sphericity of the silver powder.

[0027] 3. The present application ensures the full progress of the reduction reaction by controlling the mass ratio of the reducing liquid to the reaction liquid within a certain range, thereby improving the yield and purity of the silver powder, and at the same time helping to form uniform silver powder particles and reduce agglomeration.

[0028] 4. This application ensures good bonding between the silver powder and the dielectric material by controlling the median particle size of the micron-grade silver powder to be below 3.0 μm, reduces shrinkage and cracks after firing, and is suitable for screen printing processes, especially for printing of finer wire diameters of about 15 μm. This significantly improves the performance of electronic components such as multilayer inductors and magnetic beads, and promotes the miniaturization and high performance of electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the micron-sized silver powder of Example 1.

[0030] Figure 2 This is a SEM image of the micron-sized silver powder of Example 2.

[0031] Figure 3 This is a SEM image of the micron-sized silver powder of Example 3.

[0032] Figure 4 This is the SEM image of the micron-sized silver powder of Comparative Example 1.

[0033] Figure 5 This is the SEM image of the micron-sized silver powder of Comparative Example 2.

[0034] Figure 6 This is the SEM image of the micron-sized silver powder of Comparative Example 3.

[0035] Figure 7 This is the SEM image of the micron-sized silver powder of Comparative Example 4.

[0036] Figure 8 This is the SEM image of the micron-sized silver powder of Comparative Example 5.

[0037] Fig. 9 This is the VPSD diagram of the internal electrode conductive silver paste of Application Example 1.

[0038] Fig.10 This is the VPSD diagram of the internal electrode conductive silver paste of Application Example 2.

[0039] Fig.11 This is the VPSD diagram of the internal electrode conductive silver paste of Application Example 3.

[0040] Fig.12 This is the VPSD diagram of the internal electrode conductive silver paste of comparative application example 1.

[0041] Fig.13 This is the VPSD diagram of the internal electrode conductive silver paste of comparative application example 2.

[0042] Fig.14 This is the VPSD diagram of the internal electrode conductive silver paste of comparative application example 3.

[0043] Fig.15This is the VPSD diagram of the internal electrode conductive silver paste of comparative application example 4.

[0044] Fig.16 This is the VPSD diagram of the internal electrode conductive silver paste of comparative application example 5.

[0045] Fig.17 This is the TMA firing shrinkage curve of the internal electrode conductive silver paste of Application Example 1.

[0046] Fig.18 This is the TMA firing shrinkage curve of the internal electrode conductive silver paste of Application Example 2.

[0047] Fig.19 This is the TMA firing shrinkage curve of the internal electrode conductive silver paste of Application Example 3.

[0048] Fig. 20 This is the TMA sintering shrinkage curve of the internal electrode conductive silver paste of comparative application example 1.

[0049] Fig.21 This is the TMA firing shrinkage curve of the internal electrode conductive silver paste of comparative application example 2.

[0050] Fig. 22 This is the TMA sintering shrinkage curve of the internal electrode conductive silver paste of comparative application example 3.

[0051] Fig.23 This is the TMA firing shrinkage curve of the internal electrode conductive silver paste of comparative application example 4.

[0052] Fig.24 This is the TMA firing shrinkage curve of the internal electrode conductive silver paste of comparative application example 5.

[0053] Fig.25 This is a printing effect diagram of the internal electrode conductive silver paste of Application Example 1.

[0054] Fig.26 This is a printing effect diagram of the internal electrode conductive silver paste of Application Example 2.

[0055] Fig. 27 This is a printing effect diagram of the internal electrode conductive silver paste of Application Example 3.

[0056] Fig.28 This is a diagram showing the printing effect of the conductive silver paste for the inner electrode of comparative application example 1.

[0057] Fig.29 This is a printing effect diagram of the internal electrode conductive silver paste of comparative application example 2.

[0058] Fig.30 This is a diagram showing the printing effect of the conductive silver paste for the inner electrode of comparative application example 3.

[0059] Fig.31This is a diagram showing the printing effect of the conductive silver paste for the inner electrode of comparative application example 4.

[0060] Fig.32 This is a diagram showing the printing effect of the conductive silver paste for the inner electrode of comparative application example 5. DETAILED DESCRIPTION

[0061] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0062] Example 1 A method for preparing micron-sized silver powder comprises the following steps: Step 1: Dissolve 400 g of silver nitrate in 1800 g of water, and add 400 g of 25% (w / w) ammonia water to prepare a reaction solution.

[0063] Step 2: Dissolve 40 g of glucose, 30 g of hydroxylamine hydrochloride and 80 g of triethanolamine in 1800 g of water, adjust the pH value to 13, add 50 g of sodium hydroxide, and stir at 80 rpm for 30 min to obtain a reducing solution.

[0064] Step 3: The temperature of 2000 g of reducing solution and 2600 g of reaction solution were adjusted to 30° C. respectively, and then the reducing solution was completely added to the reaction solution under stirring at 50 rpm for 5 minutes to carry out reduction reaction.

[0065] Step 4: After the reducing solution is added, 1.24 g of sodium polymethacrylate and 0.76 g of N,N-dimethylstearamide are added, and stirring is continued at 50 rpm for 40 min at a temperature of 30° C. to obtain a dispersion.

[0066] Step 5: After filtering, washing and drying the dispersion, washing it twice with banana water and drying it, a micron-sized silver powder with a median particle size (D50) of less than 3.0 μm is obtained.

[0067] Example 2 A method for preparing micron-sized silver powder, which is different from that in Example 1, comprises the following steps: Step 1: Dissolve 500 g of silver nitrate in 2000 g of water, add 500 g of 25% (w / w) ammonia water to prepare a reaction solution.

[0068] Step 2: Dissolve 35 g of glucose, 45 g of hydroxylamine hydrochloride and 70 g of triethanolamine in 2000 g of water, adjust the pH value to 13.5, add 70 g of sodium hydroxide, and stir at 100 rpm for 25 min to obtain a reducing solution.

[0069] Step 3: The temperatures of 2220 g of the reducing solution and 3000 g of the reaction solution were adjusted to 35° C. respectively, and then the reducing solution was completely added to the reaction solution under stirring at 100 rpm for 8 minutes to carry out a reduction reaction.

[0070] Step 4: After the reducing solution is added, 2.55 g of sodium polymethacrylate and 1.8 g of N,N-dimethylstearamide are added, and the mixture is stirred at 100 rpm for 35 min at a temperature of 35° C. to obtain a dispersion.

[0071] Step 5: After filtering, washing and drying the dispersion, washing it twice with banana water and drying it, a micron-sized silver powder with a median particle size (D50) of less than 3.0 μm is obtained.

[0072] Example 3 A method for preparing micron-sized silver powder, which is different from that in Example 1, comprises the following steps: Step 1: Dissolve 600 g of silver nitrate in 2200 g of water, and add 600 g of 25% (w / w) ammonia water to prepare a reaction solution.

[0073] Step 2: Dissolve 30 g of glucose, 50 g of hydroxylamine hydrochloride and 75 g of triethanolamine in 2200 g of water, adjust the pH value to 14, add 90 g of sodium hydroxide, and stir at 150 rpm for 15 min to obtain a reducing solution.

[0074] Step 3: The temperatures of 2445 g of reducing solution and 3400 g of reaction solution were adjusted to 40° C. respectively, and then the reducing solution was completely added to the reaction solution under stirring at 150 rpm for 3 minutes to carry out reduction reaction.

[0075] Step 4: After the reducing solution is added, 3.84 g of sodium polymethacrylate and 3 g of N,N-dimethylstearamide are added, and stirring is continued at 150 rpm for 30 min at a temperature of 40° C. to obtain a dispersion.

[0076] Step 5: After filtering, washing and drying the dispersion, washing it twice with banana water and drying it, a micron-sized silver powder with a median particle size (D50) of less than 3.0 μm is obtained.

[0077] Comparative Example 1 A method for preparing micron-sized silver powder, which is different from Example 1 in that an equal amount of glucose is replaced by ascorbic acid in step 2.

[0078] Comparative Example 2 A method for preparing micron-sized silver powder, which is different from Example 1 in that an equal amount of hydroxylamine hydrochloride is replaced by hydroxylamine sulfate in step 2.

[0079] Comparative Example 3 A method for preparing micron-sized silver powder, which is different from Example 1 in that an equal amount of triethanolamine is replaced by ethanolamine in step 4.

[0080] Comparative Example 4 A method for preparing micron-sized silver powder, which is different from Example 1 in that in step 4, an equal amount of sodium polymethacrylate is replaced by polyvinyl pyrrolidone.

[0081] Comparative Example 5 A method for preparing micron-sized silver powder, which is different from Example 1 in that in step 4, an equal amount of N,N-dimethylstearamide is replaced by oleic acid amine.

[0082] Application Example 1 An inner electrode conductive silver paste comprises the following components: 5g of ethyl cellulose, 10g of pine alcohol, and 85g of micron-grade silver powder.

[0083] The inner electrode conductive silver paste is prepared by the following method: Batching - dispersion - pulping - filtering - stirring - semi-finished product inspection - adjustment - finished product inspection - packaging and warehousing.

[0084] Wherein, the micron-sized silver powder is prepared by Example 1.

[0085] Application Example 2 An inner electrode conductive silver paste, which is different from Application Example 1 in that the micron-sized silver powder is prepared by Example 2.

[0086] Application Example 3 An internal electrode conductive silver paste, which is different from Application Example 1 in that the micron-sized silver powder is prepared by Example 3.

[0087] Comparative application example 1 An inner electrode conductive silver paste, which is different from Application Example 1 in that the micron-sized silver powder is prepared by Comparative Example 1.

[0088] Comparative Application Example 2 An inner electrode conductive silver paste, which is different from Application Example 1 in that the micron-sized silver powder is prepared by Comparative Example 2.

[0089] Comparative Application Example 3 An inner electrode conductive silver paste, which is different from Application Example 1 in that the micron-sized silver powder is prepared by Comparative Example 3.

[0090] Comparative Application Example 4 An internal electrode conductive silver paste, which is different from Application Example 1 in that the micron-sized silver powder is prepared by Comparative Example 4.

[0091] Comparative Application Example 5 An internal electrode conductive silver paste, which is different from Application Example 1 in that the micron-sized silver powder is prepared by Comparative Example 5.

[0092] Performance Verification 1. The micron-sized silver powders obtained in Examples 1-3 and Comparative Examples 1-5 were observed under an electron microscope, and the electron microscope images were as shown in the attached figure. Figure 1-8 shown.

[0093] Specific comparative observations are attached Figure 1-8 It can be seen that the micron-sized silver powder prepared in Examples 1-3 has uniform particle distribution, smooth surface, high sphericity, good dispersibility, and is suitable for screen printing technology, so the printed pattern is full and has no lotus root nodes. However, the micron-sized silver powder in Comparative Examples 1-5 has an insufficiently smooth surface, poor dispersibility, or poor sphericity.

[0094] 2. The tap density of the micron-sized silver powder obtained in Examples 1-3 and Comparative Examples 1-5 was tested as follows: a 10 mL measuring cylinder, a 20 g silver powder sample, was vibrated evenly 2000 times, and the weight of the silver powder was calculated by the volume after vibration to obtain the tap density. Tap density ρ = mass of silver powder 20 g / volume after vibration V (mL).

[0095] The above test results are shown in Table 1.

[0096] Table 1: Group Tap density ρ(g / mL) Example 1 7.62 Example 2 7.21 Example 3 7.13 Comparative Example 1 3.32 Comparative Example 2 5.01 Comparative Example 3 4.35 Comparative Example 4 4.61 Comparative Example 5 4.15 Specifically combining the tap density ρ analysis of Examples 1-3 and Comparative Examples 1-5, it can be seen that the tap density of Examples 1-3 reaches more than 7 g / mL, while the tap density of Comparative Examples 1-5 is basically less than 5 g / ml.

[0097] 3. VPSD test was performed on the inner electrode conductive silver paste of Example 1-3 and Comparative Application Example 1-5, and the median particle size (D50) of the silver powder was specifically detected. The specific test results are shown in the attached Figure 9-16 .

[0098] By comparing the VPSD diagrams of Application Example 1-3 and Application Example 1-5, it can be seen that the micron-sized silver powder of Application Example 1-3 has good dispersibility and a more uniform particle size, and is more suitable for printing electrodes.

[0099] 4. The inner electrode conductive silver paste of Example 1-3 and Comparative Application Example 1-5 was tested for burn resistance. The samples were dried at 125°C, ground, and made into samples with a thickness of 1-2 mm and a diameter of about 3 mm. The samples were then tested with a TMA analyzer. The TMA analyzer used in this test is a Metler model. The specific test results are shown in the attached Figure 17-24 .

[0100] By comparing and observing the TMA firing shrinkage curves of Application Examples 1-3 and Comparative Application Examples 1-5, it can be seen that the starting temperature point of rapid shrinkage of the internal electrode conductive silver paste of Application Examples 1-3 and Comparative Application Example 1 is about 700°C. The starting temperature point of rapid shrinkage of the internal electrode conductive silver paste of Comparative Application Examples 2-5 is basically around 370°C, and then it continues to shrink without a plateau period, indicating that the activity of such internal electrode conductive silver paste is too high and the burning resistance is poor. The temperature point of rapid shrinkage of the inductor dielectric material co-fired with the silver electrode during the firing process is generally around 700°C, and before sintering, the strength of the dielectric is very low. If the internal electrode conductive silver paste shrinks too quickly and prematurely, it is easy to cause mismatch between the electrode and the dielectric shrinkage, resulting in cracking between the product layers. Therefore, the activity and burning resistance of the silver powder also have a great influence on the use of the internal electrode conductive silver paste. The micron-sized silver powder used in Application Examples 1-3 and Comparative Application Example 1 has good burning resistance and meets the firing conditions of the internal electrode conductive silver paste. However, the micron-sized silver powder used in Comparative Application Examples 2-5 has high activity and poor burning resistance and is not suitable for the firing conditions of the internal electrode conductive silver paste.

[0101] 5. The printing effects of the inner electrode conductive silver paste of Example 1-3 and Comparative Application Example 1-5 are compared. The specific printing effect diagram is attached. Figure 25-32 .

[0102] By comparing the printing effect pictures of application examples 1-3 and 1-5, it can be seen that the printed electrodes of application examples 1-3 are uniform and full, with clear patterns and strong three-dimensional effect. Fig.28 The marked box is the lotus root node phenomenon, which indicates that the printed electrode of the internal electrode conductive silver paste of comparative application example 1 has poor uniformity, serious lotus root nodes, and is not full enough, which may have a greater adverse effect on the electrical performance of later products. Similarly, the printed electrodes of the internal electrode conductive silver paste of comparative application examples 2-5 also have lotus root node phenomenon, which proves that the internal electrode conductive silver paste of application examples 1-3 is more suitable for printed electrodes.

[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing micron-sized silver powder, characterized in that: The following steps are involved: Step 1: Based on the mass fraction of the reaction solution, 40-60 parts of silver nitrate are dissolved in 180-220 parts of water, and 40-60 parts of 25% (w / w) ammonia water are added to prepare a reaction solution; Step 2: Based on the mass fraction of the reducing solution, 3-4 parts of glucose, 3-5 parts of hydroxylamine hydrochloride and 7-8 parts of triethanolamine are dissolved in 180-220 parts of water, and 5-10 parts of sodium hydroxide are added to adjust the pH value to prepare a reducing solution; Step 3: Under stirring, completely add the reducing solution into the reaction solution to carry out a reduction reaction; Step 4: After the reducing solution is added, sodium polymethacrylate and N,N-dimethyl stearamide are added, and the mixture is stirred evenly to obtain a dispersion, wherein the mass ratio of the silver nitrate, sodium polymethacrylate and N,N-dimethyl stearamide is 100: (0.31-0.64): (0.19-0.5); Step 5: Filter, wash and dry the dispersion to obtain micron-sized silver powder.

2. The method for preparing micron-sized silver powder according to claim 1, characterized in that: In the step 2, sodium hydroxide is added to adjust the pH value to within the range of 13-14. After the sodium hydroxide is added, stirring is performed at 50-150 rpm for 15-30 minutes to obtain a reducing solution.

3. The method for preparing micron-sized silver powder according to claim 1, characterized in that: The mass ratio of the reducing liquid to the reaction liquid in step 3 is 1:(1-1.5).

4. The method for preparing micron-sized silver powder according to claim 1, characterized in that: The step 3 is as follows: respectively adjust the temperature of the reducing solution and the reaction solution to 30-40° C., and then completely add the reducing solution to the reaction solution within 1-10 minutes under a stirring state of 50-150 rpm to carry out a reduction reaction.

5. The method for preparing micron-sized silver powder according to claim 1, characterized in that: In the step 4, continuing to stir evenly means stirring at a temperature of 30-40° C. and at a speed of 50-150 rpm for 30-40 min.

6. The method for preparing micron-sized silver powder according to claim 1, characterized in that: The step 5 is as follows: filtering, washing, and drying the dispersion, washing it twice with banana water, and drying it to obtain micron-sized silver powder.

7. The method for preparing micron-sized silver powder according to claim 1, characterized in that: The median particle size of the micron-sized silver powder is below 3.0 μm.

8. A micron-sized silver powder, characterized in that: The micron-sized silver powder is prepared by the method for preparing the micron-sized silver powder as described in any one of claims 1 to 7.

9. An application of the micron-sized silver powder as claimed in claim 8, characterized in that: Used to prepare conductive silver paste for internal electrodes.

10. The use of micron-sized silver powder according to claim 9, characterized in that: The inner electrode conductive silver paste includes the following components: 4wt%-6wt% ethyl cellulose, 8wt%-12wt% pine alcohol, and 80wt%-90wt% micron-sized silver powder.

Citation Information

Patent Citations

  • Silver paste of inner electrode for chip inductor and preparation method thereof

    CN101599349A

  • High-dispersion silver powder and solar battery electrode conductive silver paste

    CN102139368A

  • Preparation method of micron-sized high-activity spherical silver powder

    CN102699345A

  • Surface processing method of submicron silver powder

    CN102990056A

  • Preparation method of micron spherical silver powder for electroconductive silver paste

    CN103551586A